Lenvatinib plus anti-PD-1 therapy represents a feasible conversion resection strategy for patients with initially unresectable hepatocellular carcinoma: A retrospective study - Yi, Yong; Sun, Bao-Ye; Weng, Jia-Lei; Zhou, Cheng; Zhou, Chen-Hao; Cai, Ming-Hao; Zhang, Jing-Yun; Gao, Hong; Sun, Jian; Zhou, Jian; Fan, Jia; Ren, Ning; et al. (Frontiers in Oncology, 2022)
Purpose: We aimed to investigate the feasibility of lenvatinib plus anti-PD-1 therapy as a downstaging conversion therapy for initially unresectable hepatocellular carcinoma (HCC). Methods: Patients with initially unresectable HCC who received combined lenvatinib and anti-PD-1 antibody between May 2020 and Jan 2022 in Zhongshan Hospital were retrospectively analyzed. Tumor response and resectability were assessed by imaging every two months according to RECIST version 1.1 and modified RECIST (mRECIST) criteria. Results: A total of 107 patients were enrolled. 30 (28%) of them received conversion surgery within 90.5 (range: 53–456) days after the initiation of lenvatinib plus anti-PD-1 therapy. At baseline, the median largest tumor diameter of these 30 patients was 9.2 cm (range: 3.5-15.0 cm), 26 patients had Barcelona Clinic Liver Cancer stage B-C, and 4 had stage A. Prior to surgery, all cases displayed tumor regression and 15 patients achieved objective response. Pathological complete response (pCR) was observed in 10 patients. No severe drug-related adverse events or surgical complications were observed. After a median follow-up of 16.5 months, 28 patients survived and 11 developed tumor recurrence. Survival analysis showed patients achieving tumor response before surgery or pCR had a longer tumor-free survival. Notably, patients with microvascular invasion (MVI) had significantly higher recurrence rate and poorer overall survival than patients without. Conclusions: Lenvatinib combined with anti-PD-1 therapy represents a feasible conversion strategy for patients with initially unresectable HCC. Patients achieving tumor responses are more likely to benefit from conversion resection to access a longer term of tumor-free survival.